Detecting Borrelia Spirochetes: A Case Study With Validation Among Autopsy Specimens - Gadila, Shiva Kumar Goud; Rosoklija, Gorazd; Dwork, Andrew J.; Fallon, Brian A.; Embers, Monica E. (Frontiers in Neurology, 2021)
The complex etiology of neurodegenerative disease has prompted studies on multiple mechanisms including genetic predisposition, brain biochemistry, immunological responses and microbial insult. In particular, Lyme disease is often associated with neurocognitive impairment with variable manifestations between patients. We sought to develop methods to reliably detect Borrelia burgdorferi, the spirochete bacteria responsible for Lyme disease, in autopsy specimens of patients with a history of neurocognitive disease. In this report, we describe the use of multiple molecular detection techniques for this pathogen and its application to a case study of a Lyme disease patient. The patient had a history of Lyme disease, was treated with antibiotics, and years later developed chronic symptoms including dementia. The patient’s pathology and clinical case description was consistent with Lewy body dementia. B. burgdorferi was identified by PCR in several CNS tissues and by immunofluorescent staining in the spinal cord. These studies offer proof of the principle that persistent infection with the Lyme disease spirochete may have lingering consequences on the CNS.